Shrinkflation: A Kind of Hidden Inflation: Examining the phenomenon of shrinkflation and its impact on consumer's purchasing power (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Shrinkflation is the hone of decreasing the size or quantity of a item whereas the cost of theitem remains the same or marginally increments. It is a combination of two words shrink and inflation=Shrinkflation. In a few cases, the term may show bringing down the quality of a item or its fixings whereasthe cost remains the same. Rs. 10- Dairy Milk was premium to eat and they have been also selling Rs. 5-but now Rs. 5- is Rs. 10- andwith much smaller size and infact they are the most shrinking size dealingcompany. I hope they will at leastallow one tooth to eat Rs. 10- chocolate. Same is the case of Choco Bar,Rs. 5- size became Rs. 10- and Rs.10- became Rs. 20-.